2022
DOI: 10.3389/fpsyg.2022.919702
|View full text |Cite
|
Sign up to set email alerts
|

Academic expectations among international students from North-Western China: A case of technology use during and post COVID-19

Abstract: This study examines the influence of the COVID-19 crisis on academic expectations among international students from north-western China. According to past studies, academic expectations are multifaceted, making it critical to test the methods employed to assess this fundamental trait. The outbreak of COVID-19 has resulted in various significant changes in education, which have shifted from traditional to online or mixed formats. As a result, examining international students' academic expectations along with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The current study was carried out to measure Yemeni University students' ASE, LOs and AC and investigate the relationships among all these variables. It is pointless to put significant effort into conducting a study if the conclusions are not somewhat valid and dependable, as efficacy assessments cannot be made with confidence in such a situation (AL-Qadri et al, 2022;Boudouaia et al, 2022). To that end, the researchers conducted several steps before the final questionnaire was administered to the sample of the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study was carried out to measure Yemeni University students' ASE, LOs and AC and investigate the relationships among all these variables. It is pointless to put significant effort into conducting a study if the conclusions are not somewhat valid and dependable, as efficacy assessments cannot be made with confidence in such a situation (AL-Qadri et al, 2022;Boudouaia et al, 2022). To that end, the researchers conducted several steps before the final questionnaire was administered to the sample of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The final version of the learning outcomes scale components of 10 items is distributed on three factors: (Cognitive outcomes = 4 items; Social outcomes = 3 items; Self-growth outcomes = 3 items). Following fit indices to evaluate the overall goodness of fit of the model were indicated to good model when CFI = 0.909, TLI = 0.904, IFI = 0.910, GFI = 0.995, SRMR = 0.058, and RMSEA = 0.054 (AL-Qadri et al, 2022). Reliability was calculated using Cronbach's alpha based on the three-factor model for developing the Academic self-efficacy scale.…”
Section: Learning Outcomes (Los)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Hair et al [ 66 ] stated that questionnaire items are good estimators when the outer loading is greater than 0.5. Then, the HTMT value was tested to determine the correlation between constructs and analyze discriminant validity [ 69 ]. Previous studies suggested the HTMT value should not be higher than 0.9, with better performance at less than 0.85.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies extensively analyzed teachers' stress, which directly affects teaching and learning activities [25,49,82]. It was observed that stress affects teachers' physical and mental health [83,84]. Excessive stressful conditions can also cause teachers' depression and reduce teaching performance, which interferes with sustainable education.…”
Section: Teachers' Stress Levelsmentioning
confidence: 99%